Intuition - Derycke, Luc 1963-; Vervoordt, Axel 1947- (AsaMER, an imprint of MER.PaperKunsthalle, 2017)
To coincide with the 2017 Venice Art Biennale, the Fondazione Musei Civici di Venezia and the Axel & May Vervoordt Foundation will present their sixth, and final, exhibition: 'Intuition'. Curated by Axel Vervoordt and Daniela Ferretti, Director of the Palazzo Fortuny, and co-curated by Dario Dalla Lana, Davide Daninos and Anne-Sophie Dusselier, the exhibition will explore how intuition has, in some form, shaped art across geographies, cultures and generations. It will bring together historic, modern and contemporary works related to the concept of intuition, dreams, telepathy, paranormal fantasy, meditation, creative power, hypnosis and inspiration. Exhibition: Palazzo Fortuny, Venice, Italy (13.05. -26.11.2017)